(untitled) (University of Khartoum Engineering Journal, 2022)
The main objective of this study is to design and develop a multi-purpose utility model for north ofKhartoum area using techniques of Geographical Information System(GIS). Moreover, the study aims toinvestigate and identify the operational development systems employing integrated utility databases for facilitiesincluding water pipelines networks, sewage system, electric networks, telephone and telecommunication networksand roads services. The second goal is to establish multi-purpose utility model to aid for management anddevelopment future plans as well as providing a requisite accuracy in a multi-purpose utility model case by designand maintenance errors resulting in great cost. The methodology of this study intends to establish a mutual globaland a local datum base map comprising all utility services in study the area and to apply the GIS analysistechniques for the management and planning of these networks with the ultimate aim of achieving easy and fastoperation, updating and maintenance of these networks . The software used is ArcGIS9.3 package fortransformation of coordinates, vectorization, editing ,Topology, retopology, addition of attribute data , andperformance of spatial analysis. An urban study area (North of Khartoum) is selected from the topographical mapprepared by Dr.M.A.Gorani and provided by the Sudan National Survey Authority (SNSA) at scale of 1:25000.Itis demarcated by the Nile avenue from the North , AlImam AlHadi road from the South, the Armed Forces bridgefrom the East, and the White Nile bridge from the West.. The urban study area covers (5.94) km2. Referencespheroid for the coordinates of the study area is Clarke 1880, Universal Transverse Mercator (UTM) Projection.Grid zone is 36, and Adindan Datum. Constructing the database for the model requires scanning from a hardcopy, transformation from machine coordinates to ground coordinates, transferring from raster to vector data, andthen manipulating the database using a GIS software. The attributes were entered using the key board. This studyshown that digital utility model analyses cannot be achieved by looking or carrying out analysis only in onedimensionality of GIS; need to employ multi-dimensional GIS to accomplish GIS-SA. It has shown how thevarious dimensionalities of GIS (2D, and 3D) can be used to accomplish specific tasks in multi-purpose utilitymodel such as exchange data in different format and analysis of the utility model at both aggregated of servicesand disaggregated with data collected by the traditional and modern methods. The study concludes that a commoncontrol room should be established to mountain and manage the utility services network. Within this model therole of the GIS is to feed the system with the exact location of the break down using detectors of water anddrainage pipelines.